Perbankan Syariah Berbasis Floating Market - Yusdani - (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2005)
Islamic economics system becomes more popular currently not only in Moslem states but also those of western. In Indonesia, the development of thought regarding the urgent need to apply economics system based on syariah is emerged at 1974. Until year 2004, the quantities of Islamic banking in Indonesia grow rapidly. But the Islamic banking system growth needs to be supported by the growth of quality system of Islamic banking. To develop syariah banking in Indonesia in the future needs to advance new strategies, beside to pay attention to spiritual market (Moslems), and also to offer the products of syariah banking to floating market, for instances to non-moslem at all provinces in Indonesia. So the benefits of syariah banking will be served not only by Moslems but also by whole Indonesian people.